QoS-prioritised media delivery with adaptive data throughput in IoT-based home networks. (11th March 2021) - Hu, Chih-Lin; Kuo, Liang-Xing; Chen, Yung-Hui; Tantidham, Thitinan; Mongkolwat, Pattanasak
To maintain network efficiency of a home network, it is crucial to moderately distribute limited data throughput and bandwidth resources to various home devices and services that require different network resource provisions. This paper accounts for QoS differentiation and fairness of network resource allocation which are essential to the design of an efficient IoT-based home media delivery mechanism against network traffic dynamics. Accordingly, our study in this paper proposes a QoS-prioritised media delivery mechanism with adaptive data throughput. This mechanism design includes several functions: assigning weights of relative importance to home service types, adjusting media quality of home services, reducing data workload against traffic congestion, and fairly distributing free bandwidth to prioritised home services. Furthermore, our study fulfills a simplified proof-of-concept implementation in a small-scaled IoT-based home network. Practical experiments can generate real measure data for performance examination. Results show that the proposed mechanism is able to sustain not only QoS differentiation like data throughput and delay, but also fair user satisfaction with comfortable media playing quality.